Digital gene expression analysis in hemocytes of the white shrimp Litopenaeus vannamei in response to low salinity stress. Issue 2 (February 2015) - Zhao, Qun; Pan, Luqing; Ren, Qin; Hu, Dongxu
Abstract The white shrimp Litopenaeus vannamei has been greatly impacted by low salinity stress. To gain knowledge on the immune response in L. vannamei under such stress, we investigated digital gene expression (DEG) in L. vannamei hemocytes using the deep-sequencing platform Illumina HiSeq 2000. In total, 38, 155 high quality unigenes with average length 770 bp were generated; 145 and 79 genes were identified up- or down-regulated, respectively. Functional categorization and pathways of the differentially expressed genes revealed that immune signaling pathways, cellular immunity, humoral immunity, apoptosis, cellular protein synthesis, lipid transport and energy metabolism were the differentially regulated processes occurring during low salinity stress. These results will provide a resource for subsequent gene expression studies regarding environmental stress and a valuable gene information for a better understanding of immune mechanisms of L. vannamei under low salinity stress.